The impact of water on firefighter protective clothing thermal performance and steam burn occurrence in firefighters - André Fonseca Malaquias (2022)
Exposure to oscillating heat fluxes while having variable water contents in the thermal protective clothing (T.P. C) is possible in a real firefighting scenario. The occurrence of steam burns becomes inevitable in certain conditions which are still unidentified in the literature. In light of such, in this study, the effect of water distribution on thermal protective clothing (T.P.C) performance is studied for various environmental conditions (i.e., fixed and transient values of heat flux). A numerical approach is used to simulate heat and mass transport in the T.P.C.. Parametric studies are performed, where the exposure heat flux (0-80 kW/m(2)) and initial quantities of water in the T.P.C. are varied and correlated with second-degree burn times. The presence of water in the outer shell increases second-degree burn times, while water in the inner layer has the opposite effect for high heat fluxes. For the tested heat fluxes, burns obtained are majorly of a scald nature. The results generated allow for identifying environmental and protective clothing conditions where steam burns may become a potential hazard. This study can directly impact the proceedings for firefighters to take in certain environmental conditions and aid in the design of more effective firefighting protective suits.